La teoría de la percepción en Hegel: una reconstrucción De la dialéctica a la lógica epistémica (Revista Eletrônica Estudos Hegelianos, 2019)
Hegel has not systematically developed a theory about the way in which perception works and its contribution to knowledge. Rather, he as offered what could be characterized as a critical analysis of the assumptions that are implicit in a series of theories of perception put forward in the Modernity and in his own era. Nevertheless one can, on the basis of Hegel’s texts, attempt a reconstruction of the central features his views about perception. Among them, there is the conviction that it is not possible to separate the epistemological enterprise from the postulation of certain metaphysical commitments and beliefs. Perception is thus placed in the threefold framework of a theory of consciousness, a conception of the "logical-ontological" (das Logische) and a view about the first-person perspective and its convictions about the way in which objective reality is constituted. On the one hand, Hegel’s epistemology leads to a radical rationalist realism that somehow continues and breaks with the tradition of Kant’s transcendental philosophy to the extent that the "categories" are constitutive of the experience but in turn are modified in the process of knowledge. Considering that at least in the phenomenological process the object constitutively exceeds every conceptual scheme, Hegel does not seem to be very far from empiricism. What Hegel criticizes in it is its dogmatic conception of the ultimate components of knowledge. On the other hand, elements can be found in the Hegelian texts that show that empirical science itself necessarily establishes metaphysical claims about what "really exists", even though it is not always aware of them.